Impact of the national youth employment program "Young Productives" in the employability of the beneficiaries of Huánuco city - Rubín-Robles, Alan M. (2019)
The objective of the present investigation was to verify the impact of the National Youth Employment Program "Young Productive" in its interventions in the region Huánuco, ECAP "Aparicio Pomares", where different workshops were developed whose purpose was to train them technically and develop their employability skills . The research method used is the Scientific Method, the level of research is descriptive - correlational, the research design used in the present research was of Correlational, where it allowed us to relate with two or more data of a set of subjects with the intention To determine the subsequent relationship, which is our case. The sample of the present research work is represented by a total of 111 young people from the Zonal Unit Huánuco Youth Employment Program "Young Productive". The results obtained in the present investigation show that the majority of beneficiaries have developed employability capacities. It was concluded that there is a significant positive relationship (Pearson correlation test 0.81) between the intervention of the National Youth Employment Program "Young Productive" and the employability competencies of the beneficiaries of the Huánuco region.